EDP-514 in healthy subjects and nucleos(t)ide reverse transcriptase inhibitor-suppressed patients with chronic hepatitis B. Issue 6 (16th November 2022) - Feld, Jordan J; Lawitz, Eric; Nguyen, Tuan; Lalezari, Jacob; Hassanein, Tarek; Martin, Paul; Han, Steven-Huy; Dieterich, Douglas; Giard, Jeanne-Marie; De La Rosa, Guy; Ahmad, Alaa; Luo, Ed; et al.
Background: Chronic hepatitis B (CHB) remains a major cause of morbidity and mortality. EDP-514 is a potent core inhibitor of hepatitis B virus (HBV) that reduces viral load reduction in HBV-infected chimeric mice. This first-in-human study evaluated the safety, tolerability, and pharmacokinetics (PK) of EDP-514 in healthy subjects and antiviral activity in patients with CHB. Methods: In Part 1, 82 subjects received placebo or EDP-514 in fed or fasted state as single ascending doses of 50–800 mg and multiple ascending doses of 200–800 mg for 14 days. In Part 2, 24 HBV DNA-suppressed, nucleos(t)ide (NUC)-treated (i.e., NUC-suppressed) CHB patients received EDP-514 200–800 mg or placebo for 28 days. Results: EDP-514 was well tolerated in healthy subjects and CHB patients with most adverse events of mild intensity. In Part 1, EDP-514 exposure increased in an approximately dose proportional manner up to 600 mg after single doses and up to 400 mg after 14-day dosing. In Part 2, EDP-514 exposure increased linearly with dose on Day 1 and Day 28, with some accumulation for Day 28 and median trough concentrations (Ctrough ) approximately 20-fold above the protein-adjusted 50% effective concentration (EC50 ) for the dose range. Mean change in HBV RNA from baseline to Day 28 was −2.03, −1.67, −1.87, and −0.58 log U/mL in the 200 mg, 400 mg, 800 mg, and placebo CHB groups, respectively. Conclusions: EDP-514 was well tolerated, had a PK profile supporting once daily dosing, and reduced HBV RNA levels in NUC-suppressed CHB patients.